Como narrar a história da Revolução Russa no seu centenário? - Baña, Martín (2017)
The history of Russian Revolution was pervaded by strong ideological disputes and political interests that emerged at the height of the Cold War. The dissolution of the USSR brought several changes in theoretical perspectives, improved access to sources, and a new political context that questioned, but did not eliminate, prior prejudices. A hundred years after the Revolution, this article reviews the debates that the event inspired and analyzes the perspectives that were opened with the main transformations in the historiography of the last two decades. The objective is to present a history of the Russian Revolution that overcomes prejudices and distortions.